Smart sensors network for accurate indirect heat accounting in apartment buildings. (1st April 2022) - Stauffer, Y.; Saba, F.; Carrillo, R.E.; Boegli, M.; Malengo, A.; Hutter, A.
Abstract: A new method for accurate indirect heat accounting in apartment buildings has been recently developed by the Centre Suisse d'Electronique et de Microtechnique (CSEM). It is based on a data driven approach aimed to the smart networking of any type of indirect heat allocation devices, which can provide, for each heat delivery point of an apartment building, measurements or estimations of the temperature difference between the heat transfer fluid and the indoor environment. The analysis of the data gathered from the devices installed on the heating bodies, together with the measurements of the overall building heat consumption provided by direct heat metering, allows the evaluation of the characteristic thermal model parameters of heating bodies at actual installation and working conditions. Thus overcoming the negative impact on accuracy of conventional indirect heat accounting due to off-design operation, in which these measurement systems normally operate. The method has been tested on conventional heat cost allocators (HCA), and on innovative smart radiator thermostatic valves developed by CSEM. The evaluations were carried out at the centralized heating system mock-up of the Istituto Nazionale di Ricerca Metrologica (INRIM), and also in a real building in Neuchatel, Switzerland. The method has proven to be an effective tool to improve the accuracy of indirect heat metering systems; compared to conventional HCA systems, the error on the individual heating bill is reduced by 20%–50%. Highlights: The study presents a novel method to automatically adapt the parameters of indirect heat accounting. The method works on existing heat cost allocators' sensors as well as on smart thermostatic (radiator) valves. The study validates the method in a controlled environment. The study presents results in a non controlled environment (i.e. real building).